The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1507/endocrj.43.25
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Multiple Endocrine Neoplasia Type 2A: Genetic Analysis and Clinical Features.

Abstract: Abstract. Since a heterozygous missense mutation of the RET proto-oncogene in the germline was found to cause multiple endocrine neoplasia type 2A (MEN 2A) in 1993, some 20 different mutations of this gene have been identified in MEN 2A kindreds.We report an MEN 2A family in which serine (AGC) substitutes for cysteine (TGC) at codon 618 in exon 10 of the RET proto-oncogene. The mutation was identified by sequencing PCR products of exons 10 and 11 in the proband. Since this mutation results in creation of a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has been reported that mutations at codon 618 lead to a mild form of disease12–14. In one of these reports it was suggested that prophylactic thyroidectomy could be withheld in patients with this mutation until conventional biochemical and imaging examinations turned positive14.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that mutations at codon 618 lead to a mild form of disease12–14. In one of these reports it was suggested that prophylactic thyroidectomy could be withheld in patients with this mutation until conventional biochemical and imaging examinations turned positive14.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, almost all deaths associated with MEN2A syndromes depend on the aggressiveness of the MTC. Two reports13, 14 claiming that the 618 mutation is linked with mild MTC contained 11 and seven patients with 618 mutations respectively, but no follow‐up data were presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation